Distance-dependent migration intention of villagers: Comparative study of peri-urban and remote villages in Indonesia - Ar. Rohman T. Hidayat; Kenichiro Onitsuka; Corinthias P. M. Sianipar; Satoshi Hoshino (Administrative Sciences, 2022)
Rural-to-urban migration disturbs essential factors of rural development, including labor forces, land ownership, and food production. To avoid late responses to emigration, scholars have begun investigating earlier stages of rural emigration. However, prior studies have focused on a single spatial entity only while also leaning toward trends in developed countries. Therefore, this study fills gaps by focusing on the differences in migration intention between villages in less developed settings. In observing the differences, this research takes peri-urban and remote villages as cases located at different distances from their nearest urban destination. This study treats migration intention as the dependent variable while using single-indicator place attachment and multi-indicator information sources as the independent variables. This work applies the Mann-Whitney U, ANOVA, and Brown-Forsythe tests on three hypotheses. This research also uses SEM-PLS to investigate the correlation model of the observed variables for each case. The results show that information sources negatively affect migration intentions in peri-urban settings. Remote rural areas also show similar results for the information sources variable; however, place attachment in remote settings significantly contributes to migration intention. These results show that place attachment and information sources contribute differently, depending on the distance to the urban area. We argue that access to public services and infrastructure contributes to the results. The findings suggest that an increased availability of information sources impedes the formation of migration intentions. Thus, this study suggests the necessity of improving rural infrastructure and public services to improve information literacy. It helps the government control rural emigration while fulfilling its obligation for rural development. It also offers better rural livelihoods during the development progress, providing economic incentives for villagers to stay in villages.
Keywords: 350